CXCL6 antibody neutralization prevents lung inflammation and fibrosis in mice in the bleomycin model. Issue 6 (23rd August 2013) - Besnard, Anne‐Gaëlle; Struyf, Sofie; Guabiraba, Rodrigo; Fauconnier, Louis; Rouxel, Nathalie; Proost, Paul; Uyttenhove, Catherine; van Snick, Jacques; Couillin, Isabelle; Ryffel, Bernhard
Abstract : CXCL6 is expressed in the lung; its blockade reduces lung inflammation and collagen deposition in a mouse model of bleomycin‐induced pulmonary fibrosis. Abstract : IPF is a chronic, progressive pulmonary disease, leading to respiratory failure. In search of mechanisms of IPF, we used the bleomycin‐induced lung‐injury model in mice, which causes acute inflammation that may progress to chronic lung inflammation and fibrosis. Here, we asked whether CXCL6/GCP‐2, a member of the CXC chemokine superfamily, may be involved in IPF development. First, we reported an increase of CXCL6 levels in BALF from patients with IPF, as well as in the lung of mice, 24 h after bleomycin administration. To investigate whether CXCL6 played a role in experimental bleomycin‐induced pulmonary fibrosis, we treated mice with an anti‐mCXCL6 mAb that has been shown to inhibit neutrophil chemotaxis in vitro. CXCL6 antibody blockade attenuated acute inflammation with a reduced pulmonary neutrophil influx, IL‐1β, CXCL1, and TIMP‐1 production. In the later phase (14 days after bleomycin exposure), lymphocyte recruitment and fibrosis markers, such as collagen and TIMP‐1, were diminished, as well as collagen deposition and fibrotic lesion the lung. Therefore, the data suggest that CXCL6 contributes to experimental pulmonary fibrosis, and CXCL6 inhibition might be used to reduce lung toxicity associated with bleomycin treatment.